Ichthyofauna as an indicator of biotic integrity in a port region of the Amazon Coast of Maranhense, Brazil - Silva, Marcelo Henrique Lopes; Júnior, Audálio Rebelo Torres; Castro, Antonio Carlos Leal de; Azevedo, James Werllen de Jesus; Silva, Scarleth Patrícia Salomão da; Silva, Filipe França dos Santos; Ferreira, Larissa Gabrielle Pinheiro; Carvalho, Marina Rocha de; Mendes, Danielle Viana; Neta, Raimunda Nonata Fortes Carvalho (Seven Editora, 2024)
The objective of this study was to evaluate the environmental quality of an estuarine region located in the port area of the Amazon Coast of Maranhão, based on the calculation of a biological integrity index (IIB) that uses ichthyofauna data as parameters. Fish were collected from May 2011 to November 2015 at 4 points (P1, P2, P3 and P4) with the aid of gillnets, with meshes ranging from 18 mm to 60 mm between opposite nodes. To calculate the IIB, attributes inherent to the local ichthyofauna were chosen and categories of biotic integrity (Excellent, Good, Fair, Poor, Very Poor and No Fish) were defined. A total of 56 fish species belonging to 15 orders were recorded. The family Sciaenidae had the largest number of species, the other families recorded were Ariidae, Carangidae, Engraulidae and Mugilidae. Carnivorous species were the most abundant with 51.79%, detritivorous totaled 32.14% and omnivorous 16.07%. The temporal and spatial analyses of the IIB indicated that the integrity classes were classified as "Poor", where the score ranged between 28 and 36. The use of the Biotic Integrity Index classified the environmental quality of São Marcos Bay as Poor, suggesting that the estuarine system has undergone environmental modifications. On the other hand, the study indicated that in the last five years the region has been showing stability, about the variation of biotic indexes. DOI:https://doi.org/10.56238/sevened2024.007-018